2019
DOI: 10.1002/lno.11335
|View full text |Cite
|
Sign up to set email alerts
|

Clonal diversity and substantial genetic divergence of the Daphnia similis species complex in Chinese lakes: Possible adaptations to the uplift of the Qinghai‐Tibetan Plateau

Abstract: Very few studies have focused on the biogeography and genetic diversity of aquatic invertebrate zooplankton from the Qinghai‐Tibetan Plateau, an important biogeographic hotspot. The geological uplift of this region created special environments requiring adaptive genetic diversification of the resident lineages. Here, we developed and used the first set of high‐resolution microsatellite markers for the Daphnia similis species complex. We screened this species in 23 (out of 303) lakes across China, covering a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…himalaya Manca, 2006and D. similoides Hudec, 1991(Xu et al, 2018. Most recently, by applying a set of high-resolution microsatellite makers, we found that D. sinensis Gu, 2013 populations from Eastern China and the Qinghai-Tibetan Plateau of Western China were genetically separated from each other (Ma et al, 2019a). However, there have been no specific studies on genetic diversity or population structure of D. magna from the Qinghai-Tibetan Plateau, or even from China overall.…”
Section: Introductionmentioning
confidence: 97%
“…himalaya Manca, 2006and D. similoides Hudec, 1991(Xu et al, 2018. Most recently, by applying a set of high-resolution microsatellite makers, we found that D. sinensis Gu, 2013 populations from Eastern China and the Qinghai-Tibetan Plateau of Western China were genetically separated from each other (Ma et al, 2019a). However, there have been no specific studies on genetic diversity or population structure of D. magna from the Qinghai-Tibetan Plateau, or even from China overall.…”
Section: Introductionmentioning
confidence: 97%
“…Climatic differences might be a substantial selective pressure on freshwater zooplankton (Pinceel et al, 2018; Vadadi‐Fueloep et al, 2012), potentially driving diversification within these populations. For example, the genetic differentiation among Chinese Daphnia sinensis populations may be attributed to the climatic differences between the Qinghai‐Tibetan Plateau and the Eastern Plain (Ma, Ni, et al, 2019). Similarly, thermal differences might serve as a driving force for genetic divergence among D. galeata populations inhabiting European lakes (Herrmann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%